Risk Analysis of Information Technology Using Si Semar Layak in Online Umrah Passport Registration - Savitri, Fania Mutiara; Fadhilah, Savira Maghfiratul; Silva, Nilta Fidya; Neha, Saniya Ovin; Albana, Hifni Syauqi; Taqiyyudin, M. Aufa (Munazzama: Journal of Islamic Management and Pilgrimage, 2024)
This study aims to identify potential risks and provide a foundation for developing effective mitigation strategies. The research employed a qualitative approach to analyze information technology risks in online Umrah passport registration. Data collection was conducted through interviews, observations, and documentation. The analysis revealed that risks in online passport registration for Umrah pilgrims include data security risks, system vulnerability risks to cyber-attacks, network infrastructure failure risks that could disrupt online access, data processing errors risks, and application vulnerability risks to hacking. Mitigation measures include enhancing data security through encryption and strong access control, implementing appropriate security measures to reduce cyber-attack risks, conducting regular data backups to anticipate system failures, improving staff training and awareness on data processing, and performing regular security updates.